2018
DOI: 10.1002/aet2.10093
|View full text |Cite
|
Sign up to set email alerts
|

Brief, Web‐based Education Improves Lay Rescuer Application of a Tourniquet to Control Life‐threatening Bleeding

Abstract: Brief, Web-based training, combined with JiT education, may help as many as 75% of laypeople properly apply a tourniquet. These findings suggest that this approach may help teach the public to Stop the Bleed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…It does not provide evidence about people's ability to delineate life-threatening from non-life-threatening bleeding, although there is some evidence that the public can make this distinction. 20,21 Although tourniquet placement in the general population is considered reasonably safe for short duration applications, inappropriate tourniquet placement could cause unique harm in a vascular access population that depends on hemodialysis. 22 However, in 1 retrospective case series of 26 patients with potentially fatal vascular access hemorrhage, only 16% had tourniquet application in the ED, but all patients required emergency operating room intervention, making it unlikely that the tourniquet itself resulted in the need for surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…It does not provide evidence about people's ability to delineate life-threatening from non-life-threatening bleeding, although there is some evidence that the public can make this distinction. 20,21 Although tourniquet placement in the general population is considered reasonably safe for short duration applications, inappropriate tourniquet placement could cause unique harm in a vascular access population that depends on hemodialysis. 22 However, in 1 retrospective case series of 26 patients with potentially fatal vascular access hemorrhage, only 16% had tourniquet application in the ED, but all patients required emergency operating room intervention, making it unlikely that the tourniquet itself resulted in the need for surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…The principles used here can be extrapolated to other procedures and educational initiatives. Just-in-Time interventions have been effective for diverse fields, 9,10 with web-based interventions successful as well. 9 Emulating our principles of cost-efficiency can therefore be beneficial to many different specialties striving for procedural competence.…”
Section: Discussionmentioning
confidence: 99%
“…When those laypeople watched a brief web-based video, however, success rates increased to 75%. 31,33 A recent trial 30 found that skill degradation over time is significant and laypeople could correctly apply a tourniquet only 55% of the time 3 to 9 months after the Bleeding Control Basic course. Multiple entities have implemented either independent or modified versions of these programs, but limited evaluation beyond subjective participant or instructor feedback is available.…”
Section: Theme 3: Educationmentioning
confidence: 99%